Corneal remodeling after implantation of a shape‐changing inlay concurrent with myopic or hyperopic laser in situ keratomileusis. Issue 11 (November 2017) - Steinert, Roger F.; Koch, Douglas D.; Cochener, Beatrice; Lang, Alan; Barragán‐Garza, Enrique; Chayet, Arturo; Vargas, Luis G.
Abstract : Purpose : To compare the induced addition (add)‐power profile and epithelial remodeling between patients receiving hyperopic and myopic laser in situ keratomileusis (LASIK) concurrently with implantation of a corneal shape–changing inlay. Setting : Specialty clinics in Monterrey and Tijuana, Mexico. Design : Retrospective case series. Methods : Preoperative hyperopic patients (mean spherical equivalent [SE] treatment +1.71 diopters [D] ± 0.51 [SD]) and myopic patients (mean SE treatment −2.48 ± 1.33 D) had implantation of a Raindrop Near Vision Inlay in the nondominant eye immediately after the excimer laser ablation in both eyes under a corneal flap. Monocular and binocular visual acuities were recorded at 6 m. Wavefront measurement analysis yielded the mean inlay add‐power profile, and optical coherence tomography images yielded the mean epithelial remodeling profile. Results : In the inlay eye in the hyperopic group (n = 34) and myopic group (n = 29), the mean uncorrected near visual acuity exceeded 20/25 (85% 20/25 or better), the mean uncorrected distance visual acuity (UDVA) was 20/32 (62% 20/32 or better), and the mean binocular UDVA was 20/18 (100% 20/25 or better). The add‐power profiles for the hyperopic and myopic groups were similar. The epithelial thinning profiles were also the same, thinning centrally by approximately 19 μm, and were uncorrelated with the treated refractive error. Conclusions : After concurrent LASIK and inlay implantation, the visual acuity, induced add‐power profile, and epithelial remodeling were the same, regardless of hyperopic or myopic treatment.